PET Imaging of Acidic Tumor Environment With 89Zr-labeled pHLIP Probes - Bauer, David; Visca, Hannah; Weerakkody, Anuradha; Carter, Lukas M.; Samuels, Zachary; Kaminsky, Spencer; Andreev, Oleg A.; Reshetnyak, Yana K.; Lewis, Jason S. (Frontiers in Oncology, 2022)
Acidosis of the tumor microenvironment is a hallmark of tumor progression and has emerged as an essential biomarker for cancer diagnosis, prognosis, and evaluation of treatment response. A tool for quantitatively visualizing the acidic tumor environment could significantly advance our understanding of the behavior of aggressive tumors, improving patient management and outcomes. 89Zr labeled pH low insertion peptides (pHLIP) are a class of radiopharmaceutical imaging probes for the in vivo analysis of acidic tumor microenvironments via positron emission tomography (PET). Their unique structure allows them to sense and target acidic cancer cells. In contrast to traditional molecular imaging agents, pHLIP’s mechanism of action is pH dependent and does not rely on the presence of tumor-specific molecular markers. In this study, one promising acidity-imaging PET probe ([89Zr]Zr DFO-Cys-Var3) was identified as a candidate for clinical translation.